In Vitro stability of cocaine in whole blood and plasma including ecgonine as a target analyte - Skopp, Gisela; Klingmann, Andrea; Pötsch-Schneider, Lucia Edeltraud; Mattern, Rainer (Therapeutic drug monitoring, 2001)
The in vitro stability of cocaine (COC) was monitored in fresh whole blood and plasma stabilized with potassium fluoride (0.25%) for as long as 15 days. The samples were stored at 4°C, 20°C and 40°C. Additionally, fresh plasma samples containing either benzoylecgonine (BZE), ecgonine methyl ester (EME) or ecgonine (ECG) were stored at 4°C and 20°C. Data were established using subsequent solid-phase extraction procedures and high-performance liquid chromatography coupled to atmospheric pressure ionization mass spectrometry for isolation and quantitation of COC, BZE, EME, and ECG. - COC, BZE, and EME concentrations decreased with increasing storage temperature and time after an apparent first-order reaction kinetic. Only ECG appeared to be stable at storage temperatures as high as 20°C for the entire observation period. At 40°C, the amount of ECG produced from hydrolysis of COC still totalled 80% of the initial COC concentration. Hydrolysis of COC to EME occurred more rapidly in plasma than in blood. The dynamic degradation profiles obtained were dependent on the storage temperature. - The conversion of COC to BZE, EME, and ECG appeared to be stoichiometric at all time intervals at storage temperatures of 4°C and 20°C. The presence of any hydrolysis product of COC in blood or plasma constitutes confirmatory evidence of COC incorporation, and determination of ECG seems most promising even in samples stored under unfavorable conditions.